A kind of conductive EVA foam material and preparation method thereof
The conductive EVA foam material, enhanced by modified carbon fiber and POE/EPDM, addresses static electricity issues and maintains flexibility, offering stable conductivity for professional shoes and expanding footwear applications.
Patent Information
- Application Number
- CN202411409034.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Traditional EVA foam materials exhibit high volume resistivity, leading to static electricity accumulation, safety hazards, and inability to meet conductivity requirements for professional shoes, while existing conductivity enhancements compromise material lightness, flexibility, and cost-effectiveness.
A conductive EVA foam material is prepared by adding modified carbon fiber, POE, and EPDM, with a multi-step modification process involving chlorination, cinnamic acid modification, and polyaniline grafting to enhance conductivity and maintain softness and mechanical properties.
The modified carbon fiber enhances conductivity, maintains lightweight and flexible properties, and ensures long-term stability, making it suitable for professional shoes and expanding EVA foam applications in footwear.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of EVA foam materials, and in particular to a conductive EVA foam material and a preparation method thereof. Background Art
[0002] EVA (ethylene-vinyl acetate copolymer) foam material is widely used in the field of footwear due to its advantages of light weight, softness, good elasticity, strong cushioning and shock absorption, etc. Especially in the midsole and insole materials of sports shoes and casual shoes, EVA foam material shows excellent performance and high cost performance.
[0003] However, traditional EVA foam materials have a significant defect: their volume resistivity is usually around 10 14 Ω·cm or above, it is an insulating material. This characteristic may cause the following problems in the application of footwear materials: static electricity accumulation, the wearer is prone to static electricity during walking or exercise, causing discomfort; safety hazards, in some special environments (such as electronic factories, flammable and explosive areas), static electricity accumulation may cause safety accidents; functional limitations, unable to meet the conductivity requirements of some professional shoes (such as anti-static work shoes).
[0004] Therefore, developing EVA foam materials with certain conductive properties is of great significance for improving the functionality and comfort of shoe materials.
[0005] At present, the following methods are mainly used to improve the conductivity of EVA foam materials: adding conductive fillers, commonly used carbon black, carbon fiber, metal powder, etc., the advantages are obvious effects and relatively simple processes, and the disadvantages are that it may affect the lightness and flexibility of the material and increase costs; conductive coating, coating the surface of EVA foam material with conductive coating, the advantage is that it does not affect the performance of the material itself, the disadvantage is poor wear resistance and unstable long-term use effect; adding antistatic agents, using various antistatic agents, the advantage is simple processing and little effect on other properties of the material, the disadvantage is limited conductive effect and easy to be affected by environmental humidity.
[0006] Chinese patent document CN112574494A discloses an EVA foaming material and a preparation method thereof, comprising: a main material, a filler, a foaming agent, a bridging agent, a foaming promoter, a lubricant, a deodorizing dopant and a wear-resistant dopant. The main material is EVA, the filler is calcium carbonate, the foaming agent is AC-3000H, the bridging agent is a mixed component of DTAIC and BIPB, the foaming promoter is a mixed component of zinc oxide powder and zinc stearate powder, the lubricant is stearic acid lubricant, the deodorizing dopant is nano silver particles, and the wear-resistant dopant is a carbon fiber component. The preparation process needs to be carried out in sequence according to S1, S2, S3 and S4 operations. The internal structure comprises a breathable deodorizing layer and a wear-resistant layer, the breathable deodorizing layer is provided with air holes, the lower end of the breathable deodorizing layer is fixedly connected with the wear-resistant layer, and the wear-resistant layer is provided with wear-resistant holes.
[0007] However, the above-mentioned EVA foam materials still face many challenges when applied to shoe materials: how to effectively improve the conductivity while maintaining the light weight and softness of the EVA foam materials; how to ensure that the conductive components are evenly distributed during the foaming process to avoid affecting the appearance and feel of the shoe materials; how to balance multiple factors such as conductivity, mechanical properties, processing performance and cost; how to ensure the long-term stability of conductivity to meet the service life requirements of shoe materials.
[0008] Therefore, developing a new type of foaming material for shoes that has both good electrical conductivity and the original excellent properties of EVA foaming materials has important practical application value. This can not only improve the functionality and comfort of shoes, but also open up new application directions for EVA foaming materials in the footwear industry, such as the development of innovative products such as professional anti-static shoes and smart shoes. Summary of the invention
[0009] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a conductive EVA foam material and a preparation method thereof. The present invention imparts good conductivity to the material by adding modified carbon fiber while maintaining the original lightness and softness of EVA. The addition of POE and EPDM enhances the mechanical properties. The material is suitable for professional shoes such as anti-static work shoes and ordinary shoes, expanding the application of EVA in the footwear industry.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] A conductive EVA foam material is prepared from the following components in parts by weight: 60-80 parts of ethylene-vinyl acetate copolymer, 5-20 parts of POE, 5-10 parts of EPDM, 3-6 parts of foaming agent AC, 0.5-2 parts of stearic acid, 0.5-2 parts of zinc stearate, 1-3 parts of zinc oxide, 1-5 parts of dicumyl peroxide, and 3-10 parts of modified carbon fiber.
[0012] Preferably, the method for preparing the modified carbon fiber comprises the following steps:
[0013] (1) extracting the carbon fiber with an acetone solution, then washing with deionized water, drying, adding it to oxalyl chloride, stirring and reacting under a nitrogen atmosphere, filtering the product, washing with alcohol, and drying to obtain chlorinated carbon fiber;
[0014] Acylation of carbon fiber: The carboxyl group (-COOH) on the surface of carbon fiber reacts with oxalyl chloride (ClCOCOCl) to form an acyl chloride group (-COCl): R-COOH + ClCOCOCl → R-COCl + CO2 + HCl. This step increases the reactivity of the carbon fiber surface.
[0015] Preferably, in step (1), the carbon fiber has a diameter of 10-38 μm and a length of 0.5-1.5 mm.
[0016] Preferably, in step (1), the carbon fiber is extracted with acetone for 10 to 14 hours; the ratio of carbon fiber to oxalyl chloride is 10 g: 50 to 200 mL; and the stirring reaction conditions are stirring the reaction at 35 to 60° C. for 2 to 6 hours.
[0017] (2) Adding chlorinated carbon fiber and 4-hydroxycinnamic acid to dichloromethane under light-proof conditions, stirring and mixing, continuously introducing nitrogen, adding triethylamine, stirring and reacting, filtering, washing, and drying the product to obtain cinnamic acid-modified carbon fiber;
[0018] Cinnamic acid modification: The acyl chloride group on the chlorinated carbon fiber undergoes an esterification reaction with the hydroxyl group of 4-hydroxycinnamic acid: R-COCl + HO-C6H4-CH=CH-COOH → R-COO-C6H4-CH=CH-COOH + HCl. Triethylamine acts as a base to neutralize the HCl produced in the reaction and promote the reaction.
[0019] Preferably, in step (2), the amount ratio of chlorinated carbon fiber, 4-hydroxycinnamic acid, and dichloromethane is 10 g: 5-12 g: 50-100 mL; and the amount of triethylamine is 1-5 wt % of 4-hydroxycinnamic acid.
[0020] Preferably, in step (2), the stirring reaction conditions are 50-80° C. for 4-12 h.
[0021] (3) Add cinnamic acid-modified carbon fiber and polyaniline to DMF under light-proof conditions, stir and mix, continuously introduce nitrogen, add DCC, stir to react, filter, wash and dry the product to obtain modified carbon fiber.
[0022] Polyaniline grafting: DCC first reacts with the carboxyl group to form an O-acylisourea intermediate, and then this intermediate reacts with the amino group of polyaniline to form an amide bond and release DCU at the same time: R-COO-C6H4-CH=CH-COOH + H2N-polyaniline + DCC→ R-COO-C6H4-CH=CH-CONH-polyaniline + DCU (dicyclohexylurea).
[0023] Preferably, in step (3), the polyaniline is 5000-50000 Da, and PDI<2.
[0024] Preferably, in step (3), the dosage ratio of cinnamic acid modified carbon fiber, polyaniline and DMF is 10 g: 5-15 g: 100-200 mL; the dosage of DCC is 5-10 wt % of the polyaniline.
[0025] Preferably, in step (3), the stirring reaction conditions are 60-100° C. for 6-18 h.
[0026] The present invention also claims protection for a preparation method of the conductive EVA foam material, comprising the following steps: after the raw materials are evenly mixed, they are placed in a preheated extruder, the temperature of each zone is 110-120°C, and extrusion and mixing is performed at 20-50r / min; the obtained mixture is transferred to an open mill and mixed for 10-30 minutes, and then pressed into 3-5mm thin sheets or granules, and placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 2-12MPa and 165-180°C for 8-16 minutes to obtain the conductive EVA foam material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention provides a conductive EVA foam material, which is mainly composed of ethylene-vinyl acetate copolymer and is matched with an appropriate amount of foaming agent AC, stearic acid, zinc stearate, zinc oxide and diisopropylbenzene peroxide, so as to ensure the good foaming performance and basic physical properties of the material. In particular, modified carbon fiber is added to successfully achieve a balance between the conductive performance and the original excellent properties of EVA. The material not only maintains the characteristics of EVA foam material, such as light weight, softness, good elasticity and strong buffering and shock absorption, but also has good conductive performance, effectively solving the problem of static electricity accumulation. By optimizing the ratio of each component, the present invention successfully develops a new material that has both the advantages of conductivity and traditional EVA, which can significantly improve the functionality and comfort of shoe materials, while meeting the requirements of professional shoes such as anti-static work shoes, and opening up a new application direction for EVA foam materials in the field of footwear. In addition, the present invention adopts conventional mixing, extrusion, refining and molding processes, and the preparation method is simple and reliable, easy to realize industrial production, and has good application prospects.
[0029] (2) The present invention provides a method for preparing modified carbon fiber. First, the surface of the carbon fiber is activated by treating with oxalyl chloride to convert the hydroxyl groups on the surface of the carbon fiber into more active acyl chloride groups. Secondly, the carbon fiber is modified by using 4-hydroxycinnamic acid. In this step, the acyl chloride groups on the surface of the carbon fiber react with the hydroxyl groups in the 4-hydroxycinnamic acid to successfully introduce optically active cinnamic acid groups, and at the same time, carboxyl groups and carbon-carbon double bond structures are introduced on the surface of the carbon fiber. Finally, the carbon fiber is further modified by polyaniline. In this step, the carboxyl groups on the surface of the cinnamic acid-modified carbon fiber react with the amino groups at the ends of the polyaniline molecular chains to form amide bonds, thereby linking the polyaniline molecules with excellent conductivity to the surface of the carbon fiber. This multi-step, multi-group-involved modification process not only significantly improves the conductivity of the carbon fiber, but also improves its compatibility and dispersibility with the EVA matrix by introducing multiple functional groups.
[0030] (3) The present invention provides a modified carbon fiber. After a three-step modification process, the carbon fiber exhibits excellent properties in many aspects: first, the modified carbon fiber has higher conductivity and can achieve good conductivity at a lower addition amount, thereby maximizing the lightweight characteristics and flexibility of the EVA foam material. Secondly, the introduced cinnamate group has excellent ultraviolet absorption capacity and a large molar absorption coefficient, which helps to improve the anti-ultraviolet performance of the EVA foam material. Furthermore, polyaniline is grafted onto the surface of the carbon fiber by 4-hydroxycinnamic acid, thereby achieving effective and uniform compounding of the polyaniline network and EVA, ensuring that the polyaniline will not migrate out of the foam material during use, and further enhancing the conductivity and antistatic ability of the material. In addition, after 4-hydroxycinnamic acid is chemically bonded to the double-bonded components in the foam material, the modified carbon fiber is endowed with excellent low migration and long-term antioxidant and antistatic properties. This multiple modification not only enhances the interaction between the carbon fiber and the EVA matrix, improves the dispersibility and interface bonding strength of the carbon fiber in the material, is conducive to forming a stable conductive network, but also ensures that the conductive EVA foam material maintains stable performance during long-term use. In summary, the modified carbon fiber of the present invention provides key technical support for the development of high-performance, multifunctional conductive EVA foam materials, and significantly improves the comprehensive performance and application value of the materials. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0032] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0033] Ethylene-vinyl acetate copolymer was purchased from DuPont, brand EVA 265;
[0034] EPDM was purchased from Dow, brand EPDM5565;
[0035] POE was purchased from Mitsui Chemicals, brand DF740.
[0036] A method for preparing a conductive EVA foam material comprises the following steps:
[0037] (1) 10 g of carbon fiber was extracted with 100 mL of acetone solution for 10-14 h, then washed with deionized water, dried, added to 50-200 mL of oxalyl chloride, stirred and reacted at 35-60 °C in a nitrogen atmosphere for 2-6 h, the product was filtered, washed with alcohol, and dried to obtain chlorinated carbon fiber;
[0038] (2) Add 10 g of chlorinated carbon fiber and 5-12 g of 4-hydroxycinnamic acid to 50-100 mL of dichloromethane under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.05-0.6 g of triethylamine, stir and react at 50-80 °C for 4-12 h, filter, wash and dry the product to obtain cinnamic acid-modified carbon fiber;
[0039] (3) Add 10 g of cinnamic acid modified carbon fiber and 5-15 g of polyaniline to 100-200 mL of DMF under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.25-1.5 g of DCC, stir and react at 60-100 °C for 6-18 h, filter, wash and dry the product to obtain modified carbon fiber;
[0040] (4) 60-80 parts of ethylene-vinyl acetate copolymer, 5-20 parts of POE, 5-10 parts of EPDM, 3-6 parts of foaming agent AC, 0.5-2 parts of stearic acid, 0.5-2 parts of zinc stearate, 1-3 parts of zinc oxide, 1-5 parts of diisopropylbenzene peroxide, and 3-10 parts of modified carbon fiber are mixed evenly and placed in a preheated extruder for extrusion and mixing at 110-120° C. and 20-50 r / min; the obtained mixture is transferred to an open mill and mixed for 10-30 minutes, and then pressed into 3-5 mm thin sheets or granules, and placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 2-12 MPa and 165-180° C. for 8-16 minutes to obtain the conductive EVA foam material.
[0041] The present invention will be further described below through specific embodiments.
[0042] Example 1
[0043] A method for preparing a conductive EVA foam material comprises the following steps:
[0044] (1) 10 g of carbon fiber was extracted with 100 mL of acetone solution for 14 h, then washed with deionized water, dried, added to 100 mL of oxalyl chloride, stirred and reacted at 60 °C in a nitrogen atmosphere for 2 h, the product was filtered, washed with alcohol, and dried to obtain chlorinated carbon fiber;
[0045] (2) Add 10 g of chlorinated carbon fiber and 12 g of 4-hydroxycinnamic acid to 100 mL of dichloromethane under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.6 g of triethylamine, stir and react at 80 °C for 4 h, filter, wash and dry the product to obtain cinnamic acid-modified carbon fiber;
[0046] (3) Add 10 g of cinnamic acid modified carbon fiber and 15 g of polyaniline to 150 mL of DMF under light-proof conditions, stir and mix, continuously introduce nitrogen, add 1.5 g of DCC, stir and react at 100 °C for 6 h, filter, wash and dry the product to obtain modified carbon fiber;
[0047] (4) 8 kg of ethylene-vinyl acetate copolymer, 2 kg of POE, 1 kg of EPDM, 0.6 kg of foaming agent AC, 0.2 kg of stearic acid, 0.2 kg of zinc stearate, 0.3 kg of zinc oxide, 0.5 kg of diisopropyl peroxide, and 1 kg of modified carbon fiber were mixed evenly and placed in a preheated extruder for extrusion and mixing at 115° C. and 40 r / min; the obtained mixture was transferred to an open mill and mixed for 20 minutes, and then pressed into a 4 mm thin sheet, which was placed in a preheated flat vulcanizer mold cavity and molded and foamed at 8 MPa and 170° C. for 12 minutes to obtain the conductive EVA foam material.
[0048] Example 2
[0049] A method for preparing a conductive EVA foam material comprises the following steps:
[0050] (1) 10 g of carbon fiber was extracted with 100 mL of acetone solution for 13 h, then washed with deionized water and dried, added to 100 mL of oxalyl chloride, stirred and reacted at 50 °C in a nitrogen atmosphere for 3 h, the product was filtered, washed with alcohol, and dried to obtain chlorinated carbon fiber;
[0051] (2) Add 10 g of chlorinated carbon fiber and 10 g of 4-hydroxycinnamic acid to 100 mL of dichloromethane under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.4 g of triethylamine, stir and react at 70 ° C for 7 h, filter, wash and dry the product to obtain cinnamic acid-modified carbon fiber;
[0052] (3) Add 10 g of cinnamic acid modified carbon fiber and 12 g of polyaniline to 150 mL of DMF under light-proof conditions, stir and mix, continuously introduce nitrogen, add 1.2 g of DCC, stir and react at 90 °C for 10 h, filter, wash and dry the product to obtain modified carbon fiber;
[0053] (4) 7.4 kg of ethylene-vinyl acetate copolymer, 1.5 kg of POE, 0.8 kg of EPDM, 0.5 kg of foaming agent AC, 0.15 kg of stearic acid, 0.15 kg of zinc stearate, 0.25 kg of zinc oxide, 0.4 kg of diisopropyl peroxide, and 0.8 kg of modified carbon fiber were mixed evenly and placed in a preheated extruder for extrusion and mixing at 115° C. and 40 r / min; the obtained mixture was transferred to an open mill and mixed for 20 minutes, granulated, placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 8 MPa and 170° C. for 12 minutes to obtain the conductive EVA foam material.
[0054] Example 3
[0055] A method for preparing a conductive EVA foam material comprises the following steps:
[0056] (1) 10 g of carbon fiber was extracted with 100 mL of acetone solution for 11 h, then washed with deionized water, dried, added to 100 mL of oxalyl chloride, stirred and reacted at 40 °C in a nitrogen atmosphere for 4 h, the product was filtered, washed with alcohol, and dried to obtain chlorinated carbon fiber;
[0057] (2) Add 10 g of chlorinated carbon fiber and 8 g of 4-hydroxycinnamic acid to 100 mL of dichloromethane under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.2 g of triethylamine, stir and react at 60 ° C for 10 h, filter, wash and dry the product to obtain cinnamic acid-modified carbon fiber;
[0058] (3) Add 10 g of cinnamic acid modified carbon fiber and 8 g of polyaniline to 150 mL of DMF under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.7 g of DCC, stir and react at 70 °C for 14 h, filter, wash and dry the product to obtain modified carbon fiber;
[0059] (4) 6.8 kg of ethylene-vinyl acetate copolymer, 1 kg of POE, 0.6 kg of EPDM, 0.4 kg of foaming agent AC, 0.1 kg of stearic acid, 0.1 kg of zinc stearate, 0.2 kg of zinc oxide, 0.3 kg of diisopropyl peroxide, and 0.5 kg of modified carbon fiber were mixed evenly and placed in a preheated extruder for extrusion and mixing at 115°C and 40 r / min; the obtained mixture was transferred to an open mill and mixed for 20 minutes, and then pressed into a 4 mm thin sheet, which was placed in a preheated flat vulcanizer mold cavity and molded and foamed at 8 MPa and 170°C for 12 minutes to obtain the conductive EVA foam material.
[0060] Example 4
[0061] A method for preparing a conductive EVA foam material comprises the following steps:
[0062] (1) 10 g of carbon fiber was extracted with 100 mL of acetone solution for 10 h, then washed with deionized water and dried, added to 100 mL of oxalyl chloride, stirred and reacted at 35 °C in a nitrogen atmosphere for 6 h, the product was filtered, washed with alcohol, and dried to obtain chlorinated carbon fiber;
[0063] (2) Add 10 g of chlorinated carbon fiber and 5 g of 4-hydroxycinnamic acid to 100 mL of dichloromethane under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.05 g of triethylamine, stir and react at 50 °C for 12 h, filter, wash and dry the product to obtain cinnamic acid-modified carbon fiber;
[0064] (3) Add 10 g of cinnamic acid modified carbon fiber and 5 g of polyaniline to 150 mL of DMF under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.25 g of DCC, stir and react at 60 °C for 18 h, filter, wash and dry the product to obtain modified carbon fiber;
[0065] (4) 6 kg of ethylene-vinyl acetate copolymer, 0.5 kg of POE, 0.5 kg of EPDM, 0.3 kg of foaming agent AC, 0.05 kg of stearic acid, 0.05 kg of zinc stearate, 0.1 kg of zinc oxide, 0.1 kg of diisopropyl peroxide, and 0.3 kg of modified carbon fiber were mixed evenly and placed in a preheated extruder for extrusion and mixing at 115°C and 40 r / min; the obtained mixture was transferred to an open mill and mixed for 20 minutes, and then pressed into a 4 mm thin sheet, which was placed in a preheated flat vulcanizer mold cavity and molded and foamed at 8 MPa and 170°C for 12 minutes to obtain the conductive EVA foam material.
[0066] Comparative Example 1
[0067] A method for preparing an EVA foam material comprises the following steps:
[0068] (1) 10 g of carbon fiber was extracted with 100 mL of acetone solution for 14 h, then washed with deionized water, dried, added to 100 mL of oxalyl chloride, stirred and reacted at 60 °C in a nitrogen atmosphere for 2 h, the product was filtered, washed with alcohol, and dried to obtain chlorinated carbon fiber;
[0069] (2) Add 10 g of chlorinated carbon fiber and 12 g of 4-hydroxycinnamic acid to 100 mL of dichloromethane under light-proof conditions, stir and mix, continuously introduce nitrogen, add 0.6 g of triethylamine, stir and react at 80 °C for 4 h, filter, wash and dry the product to obtain cinnamic acid-modified carbon fiber;
[0070] (3) 8 kg of ethylene-vinyl acetate copolymer, 2 kg of POE, 1 kg of EPDM, 0.6 kg of foaming agent AC, 0.2 kg of stearic acid, 0.2 kg of zinc stearate, 0.3 kg of zinc oxide, 0.5 kg of diisopropyl peroxide, and 1 kg of cinnamic acid modified carbon fiber were mixed evenly and placed in a preheated extruder for extrusion and mixing at 115°C and 40 r / min; the obtained mixture was transferred to an open mill and mixed for 20 minutes, and then pressed into a 4 mm thin sheet, which was placed in a preheated flat vulcanizer mold cavity and molded and foamed at 8 MPa and 170°C for 12 minutes to obtain the EVA foam material.
[0071] Comparative Example 2
[0072] A method for preparing an EVA foam material comprises the following steps:
[0073] (1) 10 g of carbon fiber was extracted with 100 mL of acetone solution for 14 h, then washed with deionized water, dried, added to 100 mL of oxalyl chloride, stirred and reacted at 60 °C in a nitrogen atmosphere for 2 h, the product was filtered, washed with alcohol, and dried to obtain chlorinated carbon fiber;
[0074] (2) 8 kg of ethylene-vinyl acetate copolymer, 2 kg of POE, 1 kg of EPDM, 0.6 kg of foaming agent AC, 0.2 kg of stearic acid, 0.2 kg of zinc stearate, 0.3 kg of zinc oxide, 0.5 kg of diisopropyl peroxide, and 1 kg of acyl chloride carbon fiber were mixed evenly and placed in a preheated extruder for extrusion and mixing at 115° C. and 40 r / min; the obtained mixture was transferred to an open mill and mixed for 20 minutes, and then pressed into a 4 mm thin sheet, which was placed in a preheated flat vulcanizer mold cavity and molded and foamed at 8 MPa and 170° C. for 12 minutes to obtain the EVA foam material.
[0075] The performance tests were performed on the EVA foam materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2. The Shore hardness was measured with reference to HG / T 2489-2007 "Test Method for Hardness of Microporous Materials for Shoes"; the permanent compression deflection was tested with reference to HG / T 2876-2009 "Test Method for Compression Deformation of Microporous Materials for Rubber and Plastic Shoes"; the tear strength was tested with reference to GB / T 529-2008 "Determination of Tear Strength of Vulcanized Rubber or Thermoplastic Rubber (Pants-shaped, Right-angled and Crescent-shaped Specimens)"; the elongation and tensile strength were tested with reference to GB / T 528-2009 "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber"; the samples were subjected to ultraviolet radiation aging test, the sample surface temperature was 60±5°C, the ultraviolet wavelength range was 280~400nm, and the irradiation intensity was 15kW·h / m 2The UV irradiation test time is 2000h. The yellowing index before and after the experiment is tested with reference to HG / T 3862-2006 "Plastic Yellowness Index Test Method"; refer to ASTM D257-2014 "Standard Test Method for DC Resistance or Conductivity of Insulating Materials" to confirm the DC voltage of 100V for the foaming material, and then measure the current and convert it into resistivity; the specific data are shown in Table 1.
[0076] Table 1 EVA foam material performance test results
[0077] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Shore Hardness 51 48 46 42 53 51 Permanent compression distortion (%) 19.3 20.1 20.8 21.2 23.4 27.6 Tear strength (N / mm) 24.1 23.5 23.2 22.6 20.7 17.4 Tensile strength(MPa) 3.6 3.4 3.1 3.1 2.6 2.1 Yellowing Index Change (ΔYI) 0.4 0.4 0.5 0.5 0.5 1.3 Surface resistance(Ω) <![CDATA[3.1×10 6 ]]> <![CDATA[3.7×10 6 ]]> <![CDATA[5.2×10 6 ]]> <![CDATA[6.3×10 6 ]]> <![CDATA[6.5×10 8 ]]> <![CDATA[1.9×10 9 ]]>
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A conductive EVA foam material, characterized in that: The invention is made of the following components by weight: 60-80 parts of ethylene-vinyl acetate copolymer, 5-20 parts of POE, 5-10 parts of EPDM, 3-6 parts of foaming agent AC, 0.5-2 parts of stearic acid, 0.5-2 parts of zinc stearate, 1-3 parts of zinc oxide, 1-5 parts of dicumyl peroxide, and 3-10 parts of modified carbon fiber; The method for preparing the modified carbon fiber comprises the following steps: (1) extracting the carbon fiber with an acetone solution, then washing with deionized water, drying, adding it to oxalyl chloride, stirring and reacting under a nitrogen atmosphere, filtering the product, washing with alcohol, and drying to obtain chlorinated carbon fiber; (2) Adding chlorinated carbon fiber and 4-hydroxycinnamic acid to dichloromethane under light-proof conditions, stirring and mixing, continuously introducing nitrogen, adding triethylamine, stirring and reacting, filtering, washing, and drying the product to obtain cinnamic acid-modified carbon fiber; (3) Add cinnamic acid-modified carbon fiber and polyaniline to DMF under light-proof conditions, stir and mix, continuously introduce nitrogen, add DCC, stir to react, filter, wash and dry the product to obtain modified carbon fiber.
2. The conductive EVA foam material according to claim 1, characterized in that: In step (1), the carbon fiber has a diameter of 10-38 μm and a length of 0.5-1.5 mm.
3. The conductive EVA foam material according to claim 1, characterized in that: In step (1), the carbon fiber is extracted with acetone for 10 to 14 hours; the ratio of carbon fiber to oxalyl chloride is 10 g: 50 to 200 mL; and the stirring reaction conditions are stirring the reaction at 35 to 60° C. for 2 to 6 hours.
4. The conductive EVA foam material according to claim 1, characterized in that: In step (2), the amount ratio of chlorinated carbon fiber, 4-hydroxycinnamic acid and dichloromethane is 10 g: 5-12 g: 50-100 mL; the amount of triethylamine is 1-5 wt% of 4-hydroxycinnamic acid.
5. The conductive EVA foam material according to claim 1, characterized in that: In step (2), the stirring reaction conditions are 50-80° C. for 4-12 h.
6. The conductive EVA foam material according to claim 1, characterized in that: In step (3), the polyaniline is 5000-50000Da and PDI<2.
7. The conductive EVA foam material according to claim 1, characterized in that: In step (3), the amount ratio of cinnamic acid modified carbon fiber, polyaniline and DMF is 10g:5~15g:100~200mL; the amount of DCC is 5~10wt% of polyaniline.
8. The conductive EVA foam material according to claim 1, characterized in that: In step (3), the stirring reaction conditions are 60-100° C. for 6-18 hours.
9. A method for preparing a conductive EVA foam material as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the raw materials uniformly and placing them in a preheated extruder, wherein the temperature of each zone is 110-120°C, and extruding and kneading is performed at 20-50 r / min; transferring the obtained mixture to an open mill, kneading for 10-30 minutes, pressing into 3-5 mm thin slices or granules, placing the mixture in a preheated flat plate vulcanizer mold cavity, and performing mold foaming for 8-16 minutes at 2-12 MPa and 165-180°C to obtain the conductive EVA foam material.